Analisis Efektivitas Media Quizizz dan Wordwall untuk Meningkatkan Minat Belajar Peserta Didik pada Pembelajaran PPKn Kelas IV SDN Manyaran 01 - Najwa Rheina Putri; Ritanur Aliya Wulandari; Susilo Tri Widodo; Rina Nuraeni; Icuk Harjuno (Departement of Mathematics Education, 2025)
This study explores the effectiveness of Quizizz and Wordwall in enhancing fourth-grade students' interest in learning Civics Education (PPKn) at SDN Manyaran 01 using the Problem-Based Learning (PBL) model. A qualitative approach was employed, utilizing observation, interviews, and questionnaires for data collection. Descriptive statistical techniques and thematic analysis were used to analyze the data. Results show that Quizizz outperforms Wordwall in boosting students' learning interest. Quizizz's gamification features, such as leaderboards and group challenges, significantly enhance active participation. Conversely, Wordwall, while interactive and enjoyable, lacks competitive elements, resulting in a less noticeable increase in engagement. Key factors supporting Quizizz include its accessibility and competitive features that foster collaboration. However, its reliance on stable internet connectivity is a limitation. In contrast, Wordwall provides an engaging learning experience but offers less flexibility in customization. Overall, Quizizz demonstrates greater effectiveness in increasing students' interest and engagement, aligning with research that highlights the benefits of game-based tools in improving student motivation and participation. This study underscores the importance of incorporating interactive and competitive elements in educational media to optimize student involvement in the learning process.